Awareness, knowledge and self-reported test rates regarding Hepatitis B in Turkish-Dutch: a survey - van der Veen Ytje JJ; Voeten Hélène ACM; de Zwart Onno; Richardus Jan (BMC, 2010)
Abstract Background Hepatitis B virus infection is an important health problem in the Turkish community in the Netherlands. To prevent transmission and progression of the disease in this community, increased screening is necessary. This study aimed to determine 1) the levels of awareness and knowledge regarding hepatitis B, comparing these in tested and non-tested Turkish-Dutch in Rotterdam; 2) the self-reported hepatitis B test status in this population, and how this is related to demographic characteristics, knowledge and awareness. Methods We conducted a postal survey amongst first and second generation migrants, aged 16 - 40 years. Results The response rate was 30.2% (n = 355 respondents). Levels of awareness and knowledge regarding hepatitis B were low, as the majority of respondents (73%) never thought about the disease and 58% of the respondents scored 5 or less out of ten knowledge items. Weighted analysis of self-reports showed a test rate of 15%, and a vaccination rate of 3%. Regression analysis showed that having been tested for hepatitis B was related to being married and higher levels of awareness and knowledge. Conclusions This study shows low levels of hepatitis B awareness and knowledge in the Turkish community in Rotterdam. Self-reported test rates are lower in people who are not currently married, and in those who have low levels of awareness and knowledge. Especially, knowledge about the consequences of hepatitis B, such as liver cancer, was lacking. Therefore, a health promotion intervention should foremost raise awareness, and increase knowledge on the seriousness of this disease.